Estudo de condições operacionais para obtenção de carbonato de cálcio precipitado - Souto, Eliane Cristina Silva (2008)
Calcium carbonate (CaCO3) is a natural occurring mineral in the form of limestone. This mineral can be grinded to produce ground calcium carbonate (GCC). Another way to obtain calcium carbonate is through a precipitation process, forming the precipitated calcium carbonate (PCC). PCC usually exhibits higher purity, brightness and opacity than GCC and it is used for various purposes, e.g. as a filler or pigment for rubber, plastics, paper, paints, etc. The industrial manufacture of PCC involves the following steps: (a) calcination of limestone to produce quicklime and carbon dioxide; (b) slaking reaction, in which the quicklime is transformed to slaked lime slurry by controlled addition of H2O; and, finally (c) the carbonation reaction, in which CO2, pure or not, is bubbled through the Ca(OH)2 suspension. The use of certain chemical additives, including the ethylenediaminetetraacetic acid (EDTA) in the precipitation process, can decrease the particle size of calcium carbonate formed. The properties of PCC products depend upon the process conditions employed during its production. Calcium carbonate exists as three polymorphs (calcite, aragonite and vaterite). Calcite has greater stability at ambient temperature and it exists in various morphologies. Thus, the objective of this work was to study the best conditions of temperature, calcium hydroxide concentration, and carbon dioxide concentration to produce PCC with high specific area and small average particle sizes. Afterwards, a statistical analysis was performed in order to optimize the process conditions. It was observed that smaller PCC particle diameters are obtained using temperature of 25.6oC, calcium hydroxide concentration of 149.9 g/L and carbon dioxide concentration of 43.3%. Higher calcium hydroxide and carbon dioxide concentrations contribute to the increase of PCC specific area. It should also be noted that the addition of 0.5% EDTA in the carbonation reaction decreases the particle diameter and the narrows the particle size distribution. Through the analysis of X-ray diffraction data, it was possible to observe that calcite particles were formed and that PCC product was pure and it did not display impurities contained in GCC.